FACTORS AFFECTING THE AUDIT QUALITY OF ROAD CONSTRUCTION PROJECTS IN VIETNAM PERFORMED BY THE STATE AUDIT (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presents the impact of variables on the quality of audit quality of road constructionprojects in Vietnam conducted by the State Audit of Vietnam. The study uses a regression modelafter testing the Cronbach Alpha scale and exploratory factor analysis EFA. The research data isbased on the survey results of 232 subjects belonging to the Department of General, State Audit ofRegion I, and specialized IV and V of the State Audit of Vietnam. The result shows that six factorshave a positive influence on the audit quality of road traffic construction projects, including (1)Legal environment for the audit of road construction projects in Vietnam, (2) The factor belongingsto the audit unit are the investor units, (3) the auditor, (4) the working conditions of the state auditorof Vietnam, (5) the time audit, (6) Quality control of audits of road traffic construction projects bythe State Audit of Vietnam